2022
DOI: 10.1039/d1nj06169k
|View full text |Cite
|
Sign up to set email alerts
|

Nanoreactor of sarcosine oxidase-embedded ZIFs activates fluorescent response for diagnosis of prostate cancer

Abstract: Sarcosine is one of the important markers in the diagnosis of prostate cancer. It is essential to explore a method detecting sarcosine in biological samples quickly and accurately for early...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…However, although the method immobilized SOX, the HRP used in the system was still in a free state. 28 Gao et al proposed a new strategy for precise construction of micro mesopores to immobilize highly stable hierarchical porous metal-organic framework (HP-Zr-MOF) channel structures for HRP and glucose oxidase, which realized the rapid detection of glucose. 29 Inspired by the aforementioned studies, as shown in Scheme 1, we utilized Zr-MOFs with peroxidase-like activity to co-encapsulate SOX as well as HRP within the metal-organic framework.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although the method immobilized SOX, the HRP used in the system was still in a free state. 28 Gao et al proposed a new strategy for precise construction of micro mesopores to immobilize highly stable hierarchical porous metal-organic framework (HP-Zr-MOF) channel structures for HRP and glucose oxidase, which realized the rapid detection of glucose. 29 Inspired by the aforementioned studies, as shown in Scheme 1, we utilized Zr-MOFs with peroxidase-like activity to co-encapsulate SOX as well as HRP within the metal-organic framework.…”
Section: Introductionmentioning
confidence: 99%
“…However, although the method immobilized SOX, the HRP used in the system was still in a free state. 28 Gao et al proposed a new strategy for precise construction of micro mesopores to immobilize highly stable hierarchical porous metal–organic framework (HP-Zr-MOF) channel structures for HRP and glucose oxidase, which realized the rapid detection of glucose. 29…”
Section: Introductionmentioning
confidence: 99%